The Perpetuation of Site-Specific Installation Artworks in Museums Staging Contemporary Art - Scholte, Tatja (Amsterdam University Press, 2022)
Site-specific installations are created for specific locations and are usually intended as temporary artworks. The Perpetuation of Site-Specific Installation Artworks in Museums: Staging Contemporary Art shows that these artworks consist of more than a singular manifestation and that their lifespan is often extended. In this book, Tatja Scholte offers an in-depth account of the artistic production of the last forty years. With a wealth of case studies the author illuminates the diversity of site-specific art in both form and content, as well as in the conservation strategies applied. A conceptual framework is provided for scholars and museum professionals to better understand how site-specific installations gain new meanings during successive stages of their biographies and may become agents for change in professional routines.